Prevalences of inherited red blood cell disorders in pregnant women of different ethnicities living along the Thailand-Myanmar border. - Bancone, G; Gilder, M; Chowwiwat, N; Gornsawun, G; Win, E; Cho, W; Moo, E; Min, A; Charunwatthana, P; Carrara, V; White, N; Nosten, F; et al. (Wellcome Trust, 2017)
Background Inherited red blood cell disorders are prevalent in populations living in malaria endemic areas; G6PD deficiency is associated with oxidant-induced haemolysis and abnormal haemoglobin variants may cause chronic anaemia. In pregnant women, microcytic anaemia caused by haemoglobinopathies mimics iron deficiency, complicating diagnosis and treatment. Anaemia during pregnancy is associated with morbidity and mortality. The aim of this study was to characterise the prevalence of G6PD deficiency and haemoglobinopathies among the pregnant population living along the Thailand-Myanmar border. Pregnant women attending antenatal clinics in this area belong to several distinct ethnic groups. Methods Data were available for 13,520 women attending antenatal care between July 2012 and September 2016. Screening for G6PD deficiency was done by fluorescent spot test routinely. G6PD genotyping and quantitative phenotyping by spectrophotometry were analysed in a subsample of women. Haemoglobin variants were diagnosed by HPLC or capillary electrophoresis and molecular methods. The prevalence and distribution of inherited red blood cell disorders was analysed with respect to ethnicity. Results G6PD deficiency was common, especially in the Sgaw Karen ethnic group, in whom the G6PD Mahidol variant allele frequency was 20.7%. Quantitative G6PD phenotyping showed that 60.5% of heterozygous women had an intermediate enzymatic activity between 30% and 70% of the population median. HbE, beta-thalassaemia trait and Hb Constant Spring were found overall in 15.6% of women. Only 45.2% of women with low percentage of HbA were carriers of mutations on the alpha globin genes. Conclusions Distribution of G6PD and haemoglobin variants varied among the different ethnic groups, but the prevalence was generally high throughout the cohort. These findings encourage the implementation of an extended program of information and genetic counselling to women of reproductive age and will help inform future studies and current clinical management of anaemia in the pregnant population in this region.